2005
DOI: 10.1192/bjp.187.48.s45
|View full text |Cite
|
Sign up to set email alerts
|

Interventions in the initial prodromal states of psychosis in Germany: concept and recruitment

Abstract: The screening procedure appears to be feasible and trial participation seems to be acceptable to a relevant proportion of people at increased risk of developing psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 27 publications
0
42
0
8
Order By: Relevance
“…74, 75 Studies were included irrespective of whether they included a control group or not. Both RCTs and cohort studies were included.…”
Section: Methodsmentioning
confidence: 99%
“…74, 75 Studies were included irrespective of whether they included a control group or not. Both RCTs and cohort studies were included.…”
Section: Methodsmentioning
confidence: 99%
“…Amisulpride was the treatment of choice for late prodromal patients in a randomized German study:66 treatment markedly enhanced the benefits of psychosocial interventions 67. There is one small study of amisulpride in first episode patients which demonstrated that after 6 months the negative symptoms and quality of life of the patients had improved 68…”
Section: Amisulpride In First Episode Schizophreniamentioning
confidence: 99%
“…Research suggests that the basal ganglia may be implicated in this neurological constitutional vulnerability, as UHR individuals show impaired neural development and neurocognitive deficits related to basal ganglia function 8,11 . Additionally, Mittal and colleagues have used observer ratings to show that movement abnormalities, closely linked to basal ganglia function, could successfully classify UHR individuals likely to convert to psychosis 8,12 . Another at risk group, nonclinical psychosis individuals who report having a psychotic-like experience at least once a year, show dyskinesia during a finger force stability task 5,13,14 .…”
Section: Introductionmentioning
confidence: 99%